Dietary intake and adherence to the 2010 Dietary Guidelines for Americans among individuals with chronic spinal cord injury: A pilot study. (November 2014) - Lieberman, Jesse; Goff, David; Hammond, Flora; Schreiner, Pamela; Norton, H. James; Dulin, Michael; Zhou, Xia; Steffen, Lyn
Abstract : Objective: To investigate dietary intake and adherence to the 2010 Dietary Guidelines for Americans in individuals with chronic spinal cord injury (SCI) and able-bodied individuals. Design: A pilot study of dietary intake among a sample of individuals with SCI >1 year ago from a single site compared with able-bodied individuals. Participants/methods: One hundred black or white adults aged 38–55 years old with SCI >1 year and 100 age-, sex-, and race-matched adults enrolled in the Coronary Artery Risk Development in Young Adults (CARDIA) study. Dietary intake was assessed by the CARDIA dietary history. Linear regression analysis was used to compare dietary intake between the subjects with SCI and those enrolled in the CARDIA study. Further, adherence to the 2010 Dietary Guidelines for dairy, fruits, and vegetables, and whole-grain foods was assessed. Results: Compared with CARDIA participants, participants with SCI consumed fewer daily servings of dairy (2.10 vs. 5.0, P < 0.001), fruit (2.01 vs. 3.64, P = 0.002), and whole grain foods (1.20 vs. 2.44 P = 0.007). For each food group, fewer participants with SCI met the recommended servings compared with the CARDIA participants. Specifically, the participants with SCI and in CARDIA who met the guidelines were, respectively: dairy, 22% vs. 54% ( P < 0.001), fruits and vegetables 39% vs. 70% ( P = 0.001), and whole-grain foods 8% vs. 69.6% ( P = 0.001). Conclusions: Compared with able-bodied individuals, SCI participants consumed fewer daily servings of fruit, dairy, and whole grain foods than proposed by the 2010 Dietary Guideline recommendations. Nutrition education for this population may be warranted.